Comparison of Polysomnographic and Portable Home Monitoring Assessments of Obstructive Sleep Apnea in Saskatchewan Women. Issue 5 (2011) - Gjevre, JA; Taylor-Gjevre, RM; Skomro, R; Reid, J; Fenton, M; Cotton, D
Abstract : OBJECTIVES: To compare a commercially available, level III in-home diagnostic sleep test (Embletta, Embletta USA) and in-laboratory polysomnography (PSG) in women with suspected obstructive sleep apnea (OSA). METHODS: Consecutive women scheduled for routine PSG testing for evaluation of clinically suspected OSA and who met inclusion/exclusion criteria, were invited to participate. An in-home Embletta portable monitor test was performed one week before or after diagnostic PSG. RESULTS: Forty-seven of 96 women who met the inclusion/exclusion criteria agreed to participate. The mean (± SD) age of the patients was 52.0±11.0 years, with a mean body mass index of 34.86±9.04 kg/m 2, and 66% (31 of 47) of patients were at high risk for OSA according to the Berlin score. Paired analysis of the overall population revealed no significant difference in mean apnea/hypopnea index (AHI) between the two diagnostic methods (P=0.475). At an AHI of ≥5, the Embletta test was highly sensitive (90.6%) in determining abnormal versus normal OSA, with a positive predictive value of 82.7%. However, a higher Embletta AHI threshold of ≥10 may be more useful, with a higher level of agreement (kappa coefficient) with PSG testing and a positive predictive value of 92.3%. The in-home study was less useful at distinguishing severe from nonsevere OSA, yielding a sensitivity of 50%. CONCLUSIONS: In women believed to be at high-risk for OSA, Embletta in-home sleep testing is useful for the detection of sleep disordered breathing.